2018
DOI: 10.3390/rs10101637
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation Optical Depth and Soil Moisture Retrieved from L-Band Radiometry over the Growth Cycle of a Winter Wheat

Abstract: L-band radiometer measurements were performed at the Selhausen remote sensing field laboratory (Germany) over the entire growing season of a winter wheat stand. L-band microwave observations were collected over two different footprints within a homogenous winter wheat stand in order to disentangle the emissions originating from the soil and from the vegetation. Based on brightness temperature (T B ) measurements performed over an area consisting of a soil surface covered by a reflector (i.e., to block the radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…Tower-based passive microwave measurements over a winter wheat (Triticum aestivum L.) field were carried out using the ELBARA-II radiometer during summer 2017 [1]. The measurements were performed at the Selhausen remote sensing field laboratory (Germany) [21].…”
Section: Experiments Description Vegetation Conditions and Datasetsmentioning
confidence: 99%
See 3 more Smart Citations
“…Tower-based passive microwave measurements over a winter wheat (Triticum aestivum L.) field were carried out using the ELBARA-II radiometer during summer 2017 [1]. The measurements were performed at the Selhausen remote sensing field laboratory (Germany) [21].…”
Section: Experiments Description Vegetation Conditions and Datasetsmentioning
confidence: 99%
“…The collected brightness temperature (T B ) data showed that the T BV measurements had a higher temporal variability with generally higher values over the entire growing period, and also a larger increase and dynamic range during crop development, compared to T BH (e.g., a STD of 18.4 K for T BH and 53 K for T BV using a 40 • incidence angle). This can be explained by the stronger vertical orientation of the wheat canopy leading to a higher emission contribution in the V polarization [1]. In addition, weekly in situ measurements of vegetation properties were performed for: leaf area index (LAI), total above ground biomass (TOB), vegetation water content (VWC), growing stages (BBCH), and vegetation height (d).…”
Section: Experiments Description Vegetation Conditions and Datasetsmentioning
confidence: 99%
See 2 more Smart Citations
“…They showed that models dealing with more complex physical phenomena, such as multiple scattering and reflections, can provide better retrievals for dense (and strongly-scattering) vegetation while giving the same results as the "Tau-Omega" model for sparse and low vegetation. Furthermore, using a passive radiometer over wheat and mustard fields, Meyer et al [10] showed the importance of using a time-, polarization-, and angle-dependent optical depth (τ) parameter at the field scale for accurate soil moisture retrieval. Although the importance of those parameters is probably less important at a large scale, these effects should probably be taken into account for multi-incidence angle radiometers such as the SMOS follow-on, SMOS-HR (with an increased resolution of 10 km [11]).…”
Section: Retrieval Approachesmentioning
confidence: 99%